2023
DOI: 10.1002/agg2.20387
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pipeline and well‐pad reclamation on topsoil properties: A meta‐analysis

Nicholas Birkhimer,
Thomas M. DeSutter,
Kyle Jore
et al.

Abstract: The development of horizontal drilling and hydraulic fracking has led to an increase in oil and natural gas extraction. Development of infrastructure to extract and transport these resources is expected to increase over the next few decades, resulting in extensive land disturbance. Although reclamation aims to sufficiently return disturbed lands to their pre‐disturbance use in an ecological sense, reclaimed rights‐of‐ways (ROW) commonly produce reduced crop yields. The objective of this study was to use meta‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…For example, Birkhimer et al (2023) and Brehm and Culman (2022) compiled the results from 20 to 26 papers, respectively, on numerous soil properties post-reclamation of pipelines and found that compaction measured as bulk density increased by 20% and 12.6%, respectively, and 40.9% for penetration resistance (PR) (Brehm & Culman, 2022). Compaction is a common problem noted by reclamation specialists, and they desire a timely method to gather data.…”
Section: Future Considerationsmentioning
confidence: 99%
“…For example, Birkhimer et al (2023) and Brehm and Culman (2022) compiled the results from 20 to 26 papers, respectively, on numerous soil properties post-reclamation of pipelines and found that compaction measured as bulk density increased by 20% and 12.6%, respectively, and 40.9% for penetration resistance (PR) (Brehm & Culman, 2022). Compaction is a common problem noted by reclamation specialists, and they desire a timely method to gather data.…”
Section: Future Considerationsmentioning
confidence: 99%